SISTEM HIMPUNAN KORUM DAN MASALAH RESOLUSI KONFLIK TERDISTRIBUSI - Febryanti Febryanti (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2014)
The aims of this study are (1) to analyze relaxation of the characteristics of distributed mutual exclusion problem of various problems of widening conflict resolution in distributed system, (2) to develop coterie set system in solving any types of conflict resolution in distributed system, (3) to analyze coterie set to solve the distributed conflict problem. The method used was literary study by collecting research materials through library journals that relevant with the subject matter i.e. quorum set system and various problems of distributed conflict resolution. The results of the research indicated that mutual exclusion (mutex) can be solved with coterie, k-mutex problem can be solved by using k-coterie, read-writer problem can be solved by using bicoteri, restricted resources problem can be solved by using (m,h,ki)-coterie. For restricted and various resources matter can be constructed with disjoint and simple uniform (m,h,k)-coterie.